A Comparison of Presidential Threshold Systems in Presidential and Vice-Presidential Elections in Indonesia and Brazil - Muhammad Zhafran Shobirin; Moh Akbar Adhiyanto; Sholeh Hoddin; Rohman, Khabib Syaikhu (CV. Pustaka Parawali, 2024)
The purpose of this comparison is the reconstruction of the law. The requirements for future presidents and vice presidential candidates are listed in Article 6a, paragraph 2. However, the pros and cons of this rule are still often raised, as it reduces the individual's right to stand as president and vice president, thus requiring legislative amendments. This research uses a method of normative law research, where the approach used in this research is a legal approach and a comparative approach. The threshold in Brazil is different from Indonesia. According to J. Mark Payne, when discussing the threshold in the presidential election, what is meant is the condition of a presidential candidate to be elected president. The threshold for elected presidents in Brazil with 50% + 1 vote is laid down in Article 147. In Indonesia, such a limit is a condition for the nomination of a President and Vice-President to advance in the contest for the election of the President and Vice-Presidents. In contrast, the threshing limit for nomination for the President of the Republic of Indonesia is in Article 222, which stipulates that the pair of candidates must be proposed by the political party or association of political parties participating in the election and meet the requirement to obtain 20% (twenty percent) of the number of seats in the House of Representatives or 25% (Twenty-five percent) from the national valid votes in the previous election of members of the House.